TỔNG HỢP CAO SU THIÊN NHIÊN LỎNG CÓ NHÓM HYDROXYL CUỐI MẠCH BẰNG PHƯƠNG PHÁP FENTON QUANG HOÁ - Hữu Lý, Phạm; Thị Bích Thanh, Đỗ; Thúy Hồng, Kim; Quang Tuấn, Lê; Tùng Sơn, Phạm; Đức Giang, Lê (Vietnam Journal of Science and Technology, 2017)
Hydroxyl-terminated liquid natural rubbers (HTLNRs) prepared by the photo Fenton reaction have been characterised by 1H-NMR, 13C-NMR, DEPT, FTIR and UV-Vis. The results showed that HTLNRs had hydroxyl end groups at both chain ends and the configuration of HTLNRs macromolecules had been maintained as that of the virgin natural rubber (NR) ones. The photo degradation reaction mechanism of the NR with photo Fention reagents to form HTLNR was also proposed and discussed